Development of Bamboo Composite: Application in UAV Structure - Nurul Syaza Fakhrurozi; Latifah Md Ariffin (Progress in Aerospace and Aviation Technology, 2024)
Due to the constant rise in the usage of non-renewable resources, composite materials made of natural fibres and plastic are now receiving a lot of attention. To maximise their performance and viability, bamboo composites for use in UAV (Unmanned Aerial Vehicle) plate constructions confront several obstacles that must be overcome. This study was conducted to fabricate the UAV plate structure by using bamboo composite. Bamboo fibre, epoxy resin, epoxy hardener, and fibre mesh are the materials required to produce the sample. The tensile strength of the bamboo fibre evaluated by using Universal Testing Machine followed by ASTM standard D638. The density test of the bamboo fibre measured by using Mettler Toledo mode XS64. As the result of the study, the bamboo composite that weighted gram per area 15 g/150cm2 has the highest tensile strength, which is 20.075 MPa and for the density test, bamboo composite that weighted per area 5 g/150cm2 is denser than other conditions which is 1.115 g/cm3.